Security and Privacy in Biometrics - Campisi, Patrizio; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Biometrics-based recognition systems offer many benefits over traditional authentication approaches. However, such systems raise new challenges related to personal data protection. This important text/reference presents the latest secure and privacy-compliant techniques in automatic human recognition. Featuring viewpoints from an international selection of experts in the field, the comprehensive coverage spans both theory and practical implementations, taking into consideration all ethical and legal issues. Topics and features: Presents a unique focus on novel approaches and new architectures for unimodal and multimodal template protection Examines signal processing techniques in the encrypted domain, security and privacy leakage assessment, and aspects of standardization Describes real-world applications, from face and fingerprint-based user recognition, to biometrics-based electronic documents, and biometric systems employing smart cards Reviews the ethical implications of the ubiquity of biometrics in everyday life, and its impact on human dignity Provides guidance on best practices for the processing of biometric data within a legal framework This timely and authoritative volume is essential reading for all practitioners and researchers involved in biometrics-based automatic human recognition. Graduate students of computer science and electrical engineering will also find the text to be an invaluable practical reference. Dr. Patrizio Campisi is a Full Professor in the Department of Engineering, Section of Applied Electronics at the University of Roma Tre, Rome, Italy.
Introduction -- Design Aspects of Secure Biometric Systems and Biometrics in the Encrypted Domain -- Beyond PKI -- Fuzzy Sketches for Protecting Biometric Templates -- Privacy Leakage in Binary Biometric Systems -- Obtaining Cryptographic Keys Using Multi-Biometrics -- Privacy-Aware Processing of Biometric Templates by Means of Secure Two-Party Computation -- Fingerprint Template Protection -- Biometric Encryption -- Smart Cards to Enhance Security and Privacy in Biometrics -- Two Efficient Architectures for Handling Biometric Data While Taking Care Of Their Privacy -- Standards for Biometric Data Protection -- Nameless and Faceless -- Best Practices for Privacy and Data Protection for the Processing of Biometric Data -- Biometrics and the Challenge to Human Rights in Europe -- Recommendations on the Use of Biometric Technology.
Keywords: Computer science; Data encryption (Computer science).; Biometrics; Social sciences -- Data processing; Computers -- Law and legislation; Computer Science; Biometrics; Data Encryption; User Interfaces and Human Computer Interaction; Computer Appl. in Social and Behavioral Sciences; Legal Aspects of Computing